2020
DOI: 10.3389/fphar.2020.588449
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming—A New Era How to Prevent and Treat Graft Versus Host Disease After Allogeneic Hematopoietic Stem Cell Transplantation Has Begun

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is the solitary therapeutic therapy for many types of hematological cancers. The benefits of this procedure are challenged by graft vs. host disease (GVHD), causing significant morbidity and mortality. Recent advances in the metabolomics field have revolutionized our understanding of complex human diseases, clinical diagnostics and allow to trace the de novo biosynthesis of metabolites. There is growing evidence for metabolomics playing a role in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 101 publications
1
18
0
Order By: Relevance
“…Interestingly, iNKT1 cells seemed to downregulate Tcon gene sets involved in oxidative phosphorylation, suggesting the induction of a metabolic switch toward glycolysis, a proinflammatory metabolic state in GVHD. 36,37 Collectively, our data confirm at the transcriptomic level that distinct iNKT sublineages differentially affect Tcon during GVHD and increase our knowledge about mechanisms involved in GVHD prevention by iNKT cells. Finally, differences in iNKT sublineage tissue migration might contribute to the differences in GVHD suppression.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, iNKT1 cells seemed to downregulate Tcon gene sets involved in oxidative phosphorylation, suggesting the induction of a metabolic switch toward glycolysis, a proinflammatory metabolic state in GVHD. 36,37 Collectively, our data confirm at the transcriptomic level that distinct iNKT sublineages differentially affect Tcon during GVHD and increase our knowledge about mechanisms involved in GVHD prevention by iNKT cells. Finally, differences in iNKT sublineage tissue migration might contribute to the differences in GVHD suppression.…”
Section: Discussionsupporting
confidence: 72%
“…Our present results suggest that the pretransplant lipidomic profiles differ between allotransplant recipients. Metabolic reprogramming is now suggested as a possible strategy for prophylaxis/treatment of GVHD [ 89 , 90 , 91 , 92 , 93 ], and our results suggest that the effect of such strategies will differ between patients and/or the optimal strategy for targeting metabolic pathways will differ between patients. Our study also suggests that pretransplant lipid levels may be used as biomarkers for the risk of GVHD and/or possibly also for subclassification of patients with regard to the possible and/or optimal use of metabolic targeting.…”
Section: Discussionmentioning
confidence: 90%
“…All of these three factors are associated with altered levels of various lipid metabolites that are important regulators of fundamental cellular functions, both in various normal cells and malignant cells. Metabolic targeting is now suggested as a possible therapeutic strategy in allotransplant recipients [ 89 , 90 , 91 , 92 , 93 , 106 , 107 ]. Our present study suggests that allotransplant recipients are heterogeneous with regard to their lipidomic profiles and their metabolic regulation, and the effect of metabolic targeting (e.g., nutritional support to increase/normalize the systemic lipid levels) and/or the optimal strategy for optimal targeting may therefore differ between patient subsets.…”
Section: Discussionmentioning
confidence: 99%
“…verified the ability of purified CD4 + iNKT cells to maintain graft-versus-tumor (GvT) effect by constructing two kinds of allogeneic hematopoietic cell transplantation (HCT) models in mice [45] . It has been reported that iNKT1 can down regulate the oxidative phosphorylation of traditional T cells, accelerate the transformation of glycolysis, and cause pro-inflammatory metabolic state, which may lead to the risk of GvHD [ 46 , 47 ]. However, iNKT cells can modulate GvHD through IL-4 production, and iNKT2 and iNKT17 are potential IL-4 producers.…”
Section: Introductionmentioning
confidence: 99%